2017
DOI: 10.1037/dev0000408
|View full text |Cite
|
Sign up to set email alerts
|

The impact of negative affect on attention patterns to threat across the first 2 years of life.

Abstract: The current study examined the relations between individual differences in attention to emotion faces and temperamental negative affect across the first two years of life. Infant studies have noted a normative pattern of preferential attention to salient cues, particularly angry faces. A parallel literature suggests that elevated attention bias to threat is associated with anxiety, particularly if coupled with temperamental risk. Examining the emerging relations between attention to threat and temperamental ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
72
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 82 publications
7
72
5
2
Order By: Relevance
“…Some have found the bias for fearful faces holds at 36 months of age (Leppänen et al ., ), and others showed a decline in looking times for fearful faces between seven and 24 months of age (Peltola et al ., ). Other investigators who examined infants from 4–24 months of age have found that infants spend a greater amount of time attending to emotional faces with age, particularly threatening faces (Pérez‐Edgar et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some have found the bias for fearful faces holds at 36 months of age (Leppänen et al ., ), and others showed a decline in looking times for fearful faces between seven and 24 months of age (Peltola et al ., ). Other investigators who examined infants from 4–24 months of age have found that infants spend a greater amount of time attending to emotional faces with age, particularly threatening faces (Pérez‐Edgar et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…It remains unclear whether this attentional bias is maintained over time. Findings from recent longitudinal studies have shown that the preference to look at threatening stimuli is maintained over time (Leppänen et al ., ; Nakagawa & Sukigara, ; Pérez‐Edgar et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…For example, a recent eye‐tracking study using an infant version of the dot‐probe paradigm reported that dwell time to angry faces increases with age in a sample of 4‐ to 24‐month infants. The effect of age was not significant for happy faces (Pérez‐Edgar et al, ). Furthermore, a related study found an age‐related increase in probe fixation latency after infants fixated face pairs containing an emotional face, but not after trials with nonsocial threats (e.g., snakes) (LoBue, Buss, Taber‐Thomas, & Pérez‐Edgar, ).…”
Section: Introductionmentioning
confidence: 98%
“…The effect of NA may change with maturation (e.g., Nakagawa & Sukigara, ) and NA moderates age‐related differences in threat bias in 4‐ to 24‐month‐olds. That is, the relation between dwell time to angry faces and subsequent face disengagement is dependent on levels of NA only for younger infants (Pérez‐Edgar et al, ). While LoBue and Pérez‐Edgar () found that high NA is linked to facilitated threat detection in childhood, we lack evidence supporting NA‐related individual differences in threat vigilance during infancy.…”
Section: Introductionmentioning
confidence: 99%
“…This study did not address other sources of variability that have been shown to impact infant emotional biases. New research suggests that infant temperament can effect attention latency and dwell time to negative displays of emotion (Pérez-Edgar et al, 2017). In addition, research has shown that maternal positive affect is related to infants looking longer to a fearful expression at 7 months as compared to a happy expression (e.g.…”
Section: Limitationsmentioning
confidence: 99%